Statistical analysis of time appearance in jurus tunggal ikatan pencak silat Indonesia in senior category - Raka Muhammad Nurul Huda; Kurniati Rahayuni; Yulingga Nanda Hanief (Sriwijaya Journal of Sport, 2023)
The Single Category Movements/Kategori Jurus Tunggal in Pencak Silat is displayed within three minutes (3:00) so it is necessary to analyze the effectiveness of time in every series of movements/jurus and in every section to achieve the time accuracy of the performance. This study aims to analyze the statistical timing of the appearance of Jurus Tunggal in adult/senior Pencak Silat athletes. The study used a quantitative descriptive method with a survey approach to determine the effectiveness of the time accuracy of the appearance of Jurus Tunggal. This research was conducted by recording the time of the whole-time demonstration of single moves using a stopwatch, also each section empty hands, golok, and long sticks; as well as the time of each jurus sequence. The results of the analysis of the demonstration time are presented as a benchmark for athletes in performing single moves effectively and on time. From an analysis of 50 videos of elite athletes' performances at events at regional and national levels including State championships, National Championships, National Students Sports week/POMNAS, pre-qualification of National sports week/PON, Prabowo Cup and PON, it was found that 40% of athletes (24 athletes) performed single moves accurately in 3 minutes, 28% less than 1 second, 12% less than 1 second, 6% less than 2 seconds, 4% less than 2 seconds, and 2% less than 5 seconds. Of the 50 performance videos, none of them exceeded the tolerance limit and did not receive penalty so that the results of the percentage time performance accuracy of 50 athlete's performance videos could be used as a benchmark for the effectiveness of the performance time per movements and per section. This article also describes in full the analysis of the average time per section and per move, the slowest and fastest times per section and per move to achieve the time accuracy of the demonstration.